MANAJEMEN PELAYANAN HAJI DI KANWIL KEMENAG KABUPATEN MANDAILING NATAL - Jasa Hasibuan, Ahmad; Arianto , Nanang; Hasibuan , Susanti (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
The main problem of this research is how is the management of services for Hajj pilgrims (Study at the Ministry of Religion of Mandailing Natal Regency)? The main problem is then broken down into several sub-problems or research questions, namely: 1) How is the management of services for Hajj pilgrims at the Mandailing Natal Regency Ministry of Religion office? 2) What are the supporting and inhibiting factors in the service of Hajj pilgrims at the Mandailing Natal Regency Ministry of Religion Office? This type of research is qualitative research with the research approach used being: Management and psychology. The data sources obtained in this research are the Head of the Hajj Organizing Section, Hajj Organizing Section Staff, and Hajj pilgrims. Furthermore, the data collection methods required in this research, the author uses interviews and documentation methods. Then, data processing and analysis techniques are carried out through three stages, namely: observation, comparative analysis, and drawing conclusions.